Latent Gains or Losses: A Gauge of Trade Policy Objective Compliance in Food and Live Animals by Ecowas Member Nations - Nyajo, D. M.; Onogwu, G. O. (Darul Yasin Al Sys, 2025)
This study examines the trade dynamics of food and live animals among Economic Community of West African States (ECOWAS) members from 2008 to 2023, focusing on the volumes of exports, imports, and net trade. The primary objective is to evaluate the latent gains and losses each member nation incurs in relation to the ECOWAS trade policy aimed at achieving zero tariffs on intra-community imports. Data were collected from the United Nations Commodity Trade (UNComtrade) through the Trade Analysis and Information System Window. The analysis involved isolating the most-favored-nation tariffs to compute the latent revenue implications for member nations, distinguishing between tariff revenue gains—taxes avoided by importing from ECOWAS—and tariff revenue losses, which represent potential earnings for exporting economies under duty-free arrangements. Findings reveal significant revenue losses for countries such as Burkina Faso, Côte d'Ivoire, Ghana, Senegal, and Nigeria, which maintain the trade liberalization policy at the expense of accruable revenues while being net exporters to other member states. Conversely, nations benefiting from net imports gain from the zero-tariff policy. The study advocates for enhanced engagement in the trade of valuable food and live animals, enabling member nations to strengthen their positions as net exporters in areas of comparative advantage. This strategic shift is essential for sustaining the sub-regional trade policy and fostering long-term growth and development through enhanced intra-regional trade.